Manajemen Kolam Renang Di Kabupaten Purworejo Tahun 2020 (Universitas Negeri Semarang, 2021)
The research objective is to determine the management of swimming pools in Purworejo Regency and to know how the supporting and inhibiting factors in managing the swimming pool. This research is a qualitative descriptive study using a survey method with data collection techniques through observation, interviews, documentation, and questionnaires. This research was conducted from February 2 to February 28, 2020. The subjects in this study were managers, administrators, and visitors. Data analysis used data reduction, display data, and conclusion drawing/verification.The results showed that the management function of swimming pool planning in Purworejo Regency was good. The functions of organizing swimming pools in Purworejo Regency were quite good. The management functions of implementing swimming pools in Purworejo Regency were quite good. The management functions of swimming pool supervision in Purworejo Regency were good. There are supporting and inhibiting factors in managing swimming pools in Purworejo Regency. The conclusion in the research is that the swimming pool management of Purworejo Regency in 2020 is said to be sufficient but not optimal because there are management functions that have not been going well.